Optimizing PV Module Efficiency: Investigating the impact of Dry and Wet Dust on Solar Panel Output Power (GUB Journal of Science and Engineering, 2024)
Solar photovoltaic modules convert sunlight into electricity through the photoelectric effect. Dust accumulation on PV modules can significantly reduce their output electrical characteristics such as voltage, current, and power. The power reduction is attributed to the decrease in the amount of light reaching the solar cells due to the absorption and scattering of light by the dust layer. The magnitude of the power reduction depends on the amount and type of dust component of the solar panel. In this work, four dust components such as red soil, sand, wood power, and bird drooping are considered to test the PV performance. An indoor experimental setup is developed to test the dust impact on the PV modules using an artificial sun simulator. Experimental shows that the effect of dust accumulation on the voltage and current characteristics of solar panels is complex and depends on various factors. The percentage of degradation of output power is measured using dust under dry and wet conditions. Moreover, different amounts of dust such as 1gm, 3gm, 5gm, 7gm, and 9gm are considered for dry conditions, and 3gm and 5gm are considered for wet conditions. Bird drop causes a maximum degradation of 24.5% in dry conditions and it reduces by 17.2% in wet conditions.GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 10(1), 2023 P 68-74